Screening experts' distributional preferences - Dominik Erharter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We study optimal direct mechanisms for a credence goods expert who can be altruistic or spiteful. The expert has private information about her distributional preferences and possibly also about her customer's needs. We introduce a method that allows the customer to offer separate contracts to different preference types and outline when separation is optimal. Furthermore, we demonstrate that the optimality of separating mechanisms is sensitive to minor changes of the customer's utility function. Additionally, we illustrate how our results extend to more than two preference types and discuss possible policy implications.
Keywords: D63; D64; L13; L15; C72; 330; other-regarding preferences; inequality aversion; credence good; principal-agent model; adverse selection; moral hazard